Using Gamification Applications to Increase The Student's Learning Activity in Digital Simulation Subjects - Ahmmadi, Wahid Nur; Ekosusilo, Madyo; Putra, Hamda Kharisma (Universitas Veteran Bangun Nusantara, 2022)
The pandemic covid-19 over the past two years made major changes in the education world especially students, at which time the practice of face-to-face learning trials took place especially in the army of veteran 1 sukoharjo. The problem with face-to-face learning is that students lack the focus of learning during the teaching process, and students are inactive or lack confidence in expressing. Suggested that the process of using elements that are implemented in each activity that has no game elements and therefore provides an unsaturated effect. The purpose of this study is to increase the activation of class x TBSM students in veteran 1 sukoharjo with application of gamonification. Research methods are class action studies, using the four stages of planning, action, observation, and reflection done with the 3 cycles of pre cycles, cycles I, and cycles ii. The subject of this study is an x TBSM student at veteran 1 sukoharjo high school. The media employed in research is kahoot! And quizziz. The instrument used is the student's activity observation sheet. The data analysis technique used is a quantitative description. The study then obtained an average value-an average of 63.24 % (active criteria) on the I cycle, then with the teacher making repairs can, increasing activation to the ii cycle 81.62%. Results from test t in pairs, score alpha 0.05 acquired.